The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1128/mcb.19.5.3808
|View full text |Cite
|
Sign up to set email alerts
|

HERF1, a Novel Hematopoiesis-Specific RING Finger Protein, Is Required for Terminal Differentiation of Erythroid Cells

Abstract: The AML1/core binding factor ␤ (CBF␤) transcription factor is essential for definitive hematopoiesis; however, the downstream pathways through which it functions remain incompletely defined. Using a differential cloning approach to define components of this pathway, we have identified a novel gene designated HERF1 (for hematopoietic RING finger 1), whose expression during development is dependent on the presence of functional AML1/CBF␤. HERF1 contains a tripartite RING finger-B box-␣-helical coiled-coil domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 46 publications
(47 reference statements)
0
52
0
Order By: Relevance
“…It has been shown that TRIM10/HERF1 expression increases dramatically in MEL cells following treatment with DMSO [1]. To determine if this enhanced expression is a direct effect of DMSO or the result of an erythroid differentiation program activated by a differentiation inducer, we measured the change in TRIM10/HERF1 steady-state mRNA expression levels in two different spleen-focus forming virus (SFFV)-MEL cell lines following treatment with either of the chemical inducers (DMSO or hexamethylene bisacetamide (HMBA)) or the physiological inducer erythropoietin (EPO) ( Figure 1A).…”
Section: Trim10/herf1 Is Upregulated In Differentiating Erythroid Celmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that TRIM10/HERF1 expression increases dramatically in MEL cells following treatment with DMSO [1]. To determine if this enhanced expression is a direct effect of DMSO or the result of an erythroid differentiation program activated by a differentiation inducer, we measured the change in TRIM10/HERF1 steady-state mRNA expression levels in two different spleen-focus forming virus (SFFV)-MEL cell lines following treatment with either of the chemical inducers (DMSO or hexamethylene bisacetamide (HMBA)) or the physiological inducer erythropoietin (EPO) ( Figure 1A).…”
Section: Trim10/herf1 Is Upregulated In Differentiating Erythroid Celmentioning
confidence: 99%
“…Knowing that TRIM10/HERF1 upregulation during terminal erythroid differentiation induces globin gene expression [1], we aimed to determine if TRIM10/HERF1 expression also modulates the erythroid splicing of exon 16. MEL cell clones stably transfected with a tetracycline (Tet)-inducible vector expressing sense TRIM10/HERF1 RNA (HERF(+) cells) were tested for their ability to regulate exon 16 splicing.…”
Section: Trim10/herf1 Is Necessary But Insufficient To Activate Hemogmentioning
confidence: 99%
See 3 more Smart Citations